SYNTHESIS OF GOLD NANOPARTICLES USING dextran AS REDUCER AND STABILIZER AGENT - DIỄM, PHAN NỮ; HÒA, TRẦN THÁI; BÌNH, TRẦN THÚC (Hue University Journal of Science: Natural Science, 2019)
Gold nanoparticles (AuNPs) in spherical shape with diameter about 6–15 nm were synthesized by chemical method, using dextran as reducer and stabilizer agent. The magnetic stirrer treats of the mixture of tetrachloroauric acid and dextran in aqueous solution at ambient temperature. The influence of reaction time, Au3+ and dextran concentration on the size of AuNPs was investigated. The microstructure of AuNPs were characterized by UV-Vis spectroscopy, X-ray diffractory and transmission electron microscopy (TEM). Results indicated that aqueous suspensions of the small and well compositional homogeneity AgNPs were obtained at room temperature, Au3+ concentration = 0.5 mM, dextran concentration = 1.0% and pH = 12. The smaller Au3+ concentration favored smaller size and conversely the smaller dextran concentration favored bigger size of AuNPs. AuNPs powders were prepared by spay drying. The purity of prepared AuNPs powders was also examined by energy dispersive X-ray (EDX) analysis. Thus, the as-prepared AuNPs stabilized by biocompatible dextran in solution and/or in powder form can be potentially applied in biomedicine and pharmaceutics.